Conflict Management Skills among Nursing Tutors Working in Nursing Colleges - Thapa, Bindu; Poudel, Amrita; K.C., Deepti; Chaudhary, Janaki; Katel, Kalpana; Poudel, Sharmila; Shrestha, Shreejana; Gurung, Sunita (International Journal of Social Sciences and Management, 2021)
Conflict can exist among individuals, educational institutions, organizations, leadership of department, between staff, students and among tutors Conflict management is the practice of being able to identify and handle conflicts sensibly, fairly and efficiently. The objective of the study is to assess the conflict management skills among nursing tutors working in nursing colleges. Descriptive cross sectional research design was adopted for this study. Census method was used to select the subjects. Data collection was done among 74 nursing tutors of Kaski district. Data was collected by using self-administered Thomas Killman conflict mode standardized tool. The study revealed that 28.78% use avoiding, 20.58% use compromising, 19.9% use accommodating, and 18.74% collaborating and 12% use competing as conflict management skill. Conclusion: Avoiding was most commonly used conflict management style by nursing tutors whereas competing is the least. Int. J. Soc. Sc. Manage. Vol. 8, Issue-2: 359-361